Remoção do corante violeta de metila por adsorção em nanotubos de titanato de hidrogênio: estudo teórico-experimental - Santos, Daniela Kelly dos (2019)
Large amounts of organic dyes are used by industries (textiles, paper, cosmetics, among others), and the textile sector is responsible for the greater production, use and disposal of effluents containing these substances. Many are the types of dyes used by industries, being methyl violet, often found in their effluents. The violet methyl dye (2B) is considered a toxicant to aquatic life by interfering with the transmission of light, hindering biological processes, harming aquatic communities. In humans, its prolonged exposure may cause irritation to the eyes and gastrointestinal tract. Based on this information, the objective of this study was to evaluate the potential for the removal of Methyl Violet (VM) dye, using hydrogen titanate nanotubes H-TiNTs as adsorbents. In the pH influence test, a higher adsorption capacity was observed at pHs of (7 to 9) with removal of up to 75% of the VM. In the kinetic studies, a chemical equilibrium was observed after 180 minutes of contact, with a maximum removal of 88% of the VM dye by H-TiNTs. Among the three kinetic models studied, the best fit R2 (0.99) was for the pseudo second order, compared to the other two applied models, pseudo first order and intraparticle diffusion. In the isothermal studies, the Langmuir model best described the adsorption process of VM dye in H-TiNTs, with R2 values equal (0.99) for all temperatures. The maximum adsorption capacity (96; 100 and 106 mg g-1) obtained from the Langmuir isothermal model at temperatures of 25, 35 and 45ºC approached the values obtained experimentally (109; 115 and 120 mg g-1) and distanced themselves from the values obtained by the Freundlich model (48,5; 51,3 and 54,8 mg g-1). Values of RL (0.27, 0.26 and 0.26) (Langmuir's constant) and 1/n (0.52, 0.54 and 0.56) (Freundlich's constant) indicated that the adsorption was favorable. It’is suggest that the model is best described by the Langmuir type isotherm, thus indicating a strong interaction between the VM dye and the H-TiNTs. In the thermodynamic studies, the negative values of ΔGº (-32.66, -33.87 and -35.01) indicate that the adsorption process of H-TiNTs for removal of the dye VM is spontaneous in nature. However, the positive value of ΔHº (2.28) indicates that the adsorption process is of endothermic nature. The present study provided an experimental basis on the adsorption process in the removal of the VM dye by H-TiNTs, which showed to be efficient, presenting high adsorptive capacity and fast adsorption rate.